Zanzibar : Can Goal-setting and Incentives Improve Student Performance? - World Bank (World Bank, Washington, DC, 2020)
The Results in Education for All Children (REACH) Trust Fund at the World Bank funded an evaluation that measured how two different incentive approaches affected the academic performance of grade 9 students in Zanzibar (Tanzania). The first approach allowed students to set personal goals at the beginning of the school year regarding their performance by the end of the year. The second approach combined this goal-setting exercise with non-financial rewards such as certificates or in-kind prizes for students who met their goals. These approaches were designed to answer the following questions: (i) whether students setting goals for themselves has any effect on their performance in school and (ii) whether this effect is strengthened when combined with non-financial incentives.